Islamic Religious Educational Issues and the Role of Stakeholders - Sudirman Sudirman; J. Nabiel Aha Putra (Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2025)
Sawohan 2 State Elementary School in Kepetingan Hamlet, a remote area on the east coast of Sidoarjo Regency, faces various challenges in implementing Islamic religious education. Its difficult to reach location and limited infrastructure have an impact on the low effectiveness of learning, especially in worship practices, learning the Qur'an, and student learning motivation. Geographical factors, minimal parental support, and limited educational infrastructure are the main obstacles. This study uses a qualitative descriptive approach, with data collection techniques through interviews, observations, and documentation. The results of the study show that the problems include the absence of worship facilities, distance and difficult access for teachers, low student participation in Islamic religious education activities, and weak evaluation and mentoring by educators. Stakeholders such as the Education Office, principals, teachers, community leaders, and parents have a strategic role in overcoming these challenges. Efforts made include: increasing physical access to schools, motivation for educators and students, providing incentives for teachers in remote areas, developing a contextual Islamic religious education curriculum, and strengthening collaboration between schools and the community.